Cardiovascular Magnetic Resonance in Myocarditis - Rizzo, Toni (MD Conference Express, 2012)
Myocarditis is a broad diagnosis based on the presence of tissue inflammation. Making a pathologic diagnosis is difficult with the nonspecific methods available. This article discusses the benefits of cardiac MRI for diagnosing myocarditis.